Comparative performance analysis of VTR and CTR in digital video advertising (Herald of Journalism, 2019)
The PR market is gaining momentum every day, and specialists in this field use new technological solutions for greater productivity. Modern PR in practice gradually goes online with the target audience. But PR and marketing as a science do not keep pace with modern realities in assessing the effectiveness of certain technological tools. Subsequently, often new untested tools lead to a loss of traffic and budget. This is what makes the goal of the study evaluating the effectiveness of advertising in digital environment relevant and significant in practice in comparison with the classical tools of PR-technologies. This article provides a comparative analysis of the effectiveness of VTR (viewability) and CTR (click-ability) in digital video advertising. Video advertising on the modern Internet and Smart TV is a frequent phenomenon and at this time is considered one of the most effective types of online advertising. Adver-tising companies and customers use CTR to a greater degree and focus on greater click-throughness of advertising. But the visibility and the moment of the effect of advertising remain outside the attention of customers and customer-oriented marketers. According to the analysis carried out, video advertising turned out to be more effective in the con-text of public relations and image than direct sales and marketing. The article also reveals the new side and analyzes the effectiveness of video advertising on CTR and VTR indicators, also provides statistical data for visual comparison. Analysis, methodology and conclusions of this work are relevant, they make a significant contribu-tion to the effectiveness of the work of specialists in the field of PR and marketing, and can also serve as educational material in the training of new specialists.
Keywords: video advertising performance, VTR, CTR, digital, image, PR, marketing.